Translator Studies on Sidney Shapiro: A Case Study of Registration - Aiqing Wang (İstanbul Üniversitesi Çeviribilim Dergisi)
As a leading figure of a distinctive literary school dubbed 山蛋派 Shanyaodan Pai ‘Potato School’, 理Zhao Shuli has composed a myriad of novellas and novels concerning peasantry, countryside and societal transformation. Three of Zhao’s fiction have been rendered into English by an illustrious translator Sidney Shapiro (aka 沙博理Sha Boli), viz. 小二黑结婚Xiaoerhei Jiehun ‘The Marriage of Young Blacky’, 孟祥英翻身Meng Xiangying Fanshen ‘Meng Xiangying Turns Over’ and 登记Dengji ‘Registration’. In this research, I investigate the English version of Registration, which has not attained deserved critical attention. I place an emphasis on translator studies, exploring the translator’s ideology, telos and stance. As a prolific translator with communist ideology, Shapiro has rendered a profusion of literary works pertaining to the Chinese Communist Party and the masses’ struggles in Anti-Japanese War of Resistance. In the target text of Registration, Shapiro manifests his aspirations to disseminate traditional and modern Chinese culture, in accordance with the party-state’s intention to enhance the country’s image upon the foundation of the People’s Republic of China in 1949.